Does farming experience matter? A comparison of farm health and safety attitudes, perceptions, and intentions of agricultural science students with and without farming experience - Mohammad Mohammadrezaei; David Meredith; Sinéad Flannery; Jim Kinsella; John McNamara (Rural and Remote Health, 2023)
Introduction: This study addresses two main questions: 'How does having the experience of farming influence college students’ intrinsic motivations towards farm health and safety (FHS)?' and 'Are there any differences between the motivations reported by students with and without having such experience?'. This study seeks to investigate the role of farming experience in students’ cognitive factors and intentions to evaluate whether sharing experiences and stories positively shape students' cognitive factors to perform FHS behaviours.Methods: A cross-sectional online survey using a semi-structured questionnaire was assigned to a nationally representative sample of agricultural science students in Ireland (n= 430). Applying independent sample t-test and ANOVA test, multiple comparisons were made to examine if having the experience of farming affects FHS intrinsic motivations.Results: This study illustrated students without farming experience are less likely to perceive farming as a dangerous occupation while they reported a slightly positive attitude and intention compared with their counterparts with experience of farming. Our study illustrated students with experience of farming gave a lower priority to FHS and control over safety behaviour (pessimistic approach) and they reported a slightly higher level of risk perception (optimistic perception).Discussion: Having experience of farming (destructive experience - the experience of farming without having a near miss or injury or having heard of accidents, ie negative factors affecting students’ motivations) may not be necessarily a positive factor as risk-taking is admitted as a norm and a part of the nature of the work. Conversely, having experience of FHS issues (constructive experience - any kind of farming experience that positively shapes students' motivations towards FHS) can positively shape attitude, perceptions, and intention. Therefore, we recommend that constructive experiences (positive affecting intrinsic motivations) should be incorporated into the FHS training of students through peer-to-peer sharing as this enhances attitudes, perceptions, and willingness of the majority of students.